ANALISIS TINGKAT KEPUASAN MASYARAKAT TERHADAP PELAYANAN PADA KANTOR IMIGRASI KELAS I KHUSUS TPI NGURAH RAI - SRIANING, NYOMAN; SANJAYA, I NYOMAN SUKA; SUBAGIANA, I GEDE MADE (Universitas Mahasaraswati K. Mataram, 2024)
This research was conducted to analyze the level of public satisfaction with services at the TPI Ngurah Rai Special Class I Immigration Office, which was motivated by the high number of complaints and requests for information as well as the lowest rating from Google reviews among other immigration offices in Bali. The results of previous research show varying results regarding the influence of tangible, reliability, responsiveness, assurance and empathy aspects on community satisfaction. The aim of this research is to determine the effect of service quality using ServQual (tangible, reliability, responsiveness, assurance and empathy) on community satisfaction at the TPI Ngurah Rai Special Class I Immigration Office partially and simultaneously. This research uses descriptive quantitative methods. The total sample was 100 respondents with sampling using the accidental sampling method. The data analysis technique uses multiple linear regression analysis with hypothesis testing using the t test and F test. The results simultaneously show that the variables tangible, reliability, responsiveness, assurance and empathy have a significant effect on community satisfaction. Partial results show that the tangible and assurance variables do not have a significant effect on community satisfaction, the empathy variable has a negative but not significant effect on community satisfaction, and the reliability and responsiveness variables have a significant influence on community satisfaction. The determination test showed that 62.9% of the variation in community satisfaction variables could be influenced by tangible, reliability, responsiveness, assurance and empathy variables.